Технологическая схема регенерации отработанных сернокислотных растворов, содержащих сульфат натрия - Булавин, Виктор Иванович; Крамаренко, Андрей Викторович; Ульянов, В. П.; Ульянова, И. В. (НТУ "ХПИ", 2015)
Предложена технологическая схема установки, обеспечивающая термическую переработку отработанных сернокислотных травильных растворов с возвратом серной кислоты в технологический цикл обработки стеклоизделий и утилизацией сульфата натрия. Схема предусматривает осветление ОР с коагуляцией органических примесей, предварительное упаривание осветленных ОР, подачу упаренных ОР в аппарат «кипящего» слоя для разделения на гранулированную твердую фазу сульфата натрия и газопаровую смесь, которая конденсируется с получением концентрированной серной кислоты, пригодной для возврата в технологический цикл. Остаточный туман серной кислоты после конденсации отфильтровывается волокнистым фильтром. Разработаны основные требования к технологическому оборудованию промышленной установки.

In this paper we propose a flowchart of the equipment providing regeneration of spent solutions after the etching of glass fiber. These solutions contain sulfuric acid and sodium sulfate. Sulfuric acid can be returned in the production cycle with utilization sodium sulfate. Processing begins with a clarification of spent solution by coagulation of organic impurities. After that clarified solution must be partially evaporated in a special acid-resistant boiler heated by gas burner. It reduces the volume of solution by several times. The hot concentrated solution then sprays via nozzles to the "fluidized" layer reactor blown with hot products of combustion. Here the solution decomposes to sulfuric acid vapor and a granular sodium sulfate. The vapor condenses giving a concentrated sulfuric acid suitable for recycling. Residual sulfuric acid fog after the condensation can be eliminated by fibrous filter. The basic requirements to the industrial equipment for regeneration are developed.
Technological scheme of regeneration of spent sulfuric acid solutions containing sodium sulfate
Keywords: раствор травильный; стекловолокно; слой кипящий; etching solution; glass fibers; fluidized layer